Relationship between adenosine deaminase polymorphism (c.22G > A) and oxidative stress in sickle cell anemia - da Silva, Danilo Grï¿½nig Humberto [UNESP]; Belini-Junior, Edis [UNESP]; de Souza Torres, Lidiane [UNESP]; Okumura, Jessika Viviani [UNESP]; Barberino, Willian Marcel [UNESP]; de Oliveira, Renan Garcia [UNESP]; Teixeira, Vanessa Urbinatti [UNESP]; de Castro Lobo, Clarisse Lopes; de Almeida, Eduardo Alves [UNESP]; Bonini-Domingos, Claudia Regina [UNESP] (Elsevier, 2017)
The aim of this study was to identify, in people with sickle cell anemia (SCA), adenosine deaminase (ADA; c. 22G > A; rs73598374) polymorphism, and correlating it with oxidative stress markers. We evaluated 95 unrelated and diagnosed Brazilian sickle cell anemia (SCA) patients. All patients received a prophylactic treatment with folic acid of 5 mg/day, while 41 (43.2%) of them were under hydroxycarbamide (HC) treatment (average dose: 22 mg/kg/day). ADA polymorphism was identified by PCR-RFLP. Biochemical parameters were measured using spectrophotometric [catalase, glutathione S-transferase, glutathione peroxidase, glutathione reductase activities] and chromatographic methods [fetal hemoglobin (HbF), glutathione (GSH) and malondialdehyde (MDA) levels]. Among the 95 SCA patients, we identified 80 (84.2%) wild homozygous for ADA (22GG), 15 (15.8%) heterozygous (22GA) and none mutant homozygous (22AA), leading to an allelic frequency of 0.92 for the ancestral allele (22G) and 0.08 for the mutant one (22A). Unexpectedly, we did not observe any influence of ADA polymorphism on oxidative stress markers, as well as interaction effects with HC usage. However, we confirmed a well-described protective effect of HC treatment on decreasing MDA levels (p = 0.03). Thus, we concluded that ADA (22G > A) polymorphism does not play significant role in the disruption of sickle erythrocyte redox metabolism.
Keywords: Adenosine; Fetal hemoglobin; Hemoglobin S; Hydroxycarbamide